Les pratiques musicales autochtones : une confluence de perspectives - Beaudry, Nicole (Traité de la culture, 2002)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.